Compliance of the regulatory accounting framework of fixed assets in the Republic of Croatia and Bosnia and Herzegovina - Aljinović Barać, Željana; Porobija, Tea (Oeconomica Jadertina, 2021)
The subject of this paper is to determine the level of compliance or harmonisation of the applicable regulatory framework (accounting standards) in the recognition and measurement of various categories of fixed assets in the Republic of Croatia (RH) and Bosnia and Herzegovina (BiH). The conducted research established a 93% compliance of the regulatory framework and proved that the regulatory framework of accounting recognition and measurement of fixed assets in the Republic of Croatia and Bosnia and Herzegovina coincided in 13 of the 14 analyzed areas of valuation of fixed assets. Empirical verification of the used accounting policies among listed companies in the Republic of Croatia and Bosnia and Herzegovina confirmed the existence of significant differences in the accounting policies of valuation of real estate, plant and equipment and agriculture, in particular biological assets. On the other hand, in the area of subsequent valuation of real estate investments, applied depreciation methods and valuation of agricultural products derived from biological assets, we found that statistically significant differences in the used accounting policies between companies in the Republic of Croatia and Bosnia and Herzegovina did not exist. The obtained results should primarily facilitate the comparability of financial statements of companies in the Republic of Croatia and Bosnia and Herzegovina, and thus consequently and positively affect the increase in capital flows between these two neighbouring countries. In the scientific context, this research represents asignificant contribution to the scarce literature on this topic.
Keywords: regulatory framework; accounting standards; fixed assets; Croatia; Bosnia and Herzegovina